2017
DOI: 10.1002/ccd.27178
|View full text |Cite
|
Sign up to set email alerts
|

Midterm to long‐term safety and efficacy of self‐expandable nitinol stent implantation for coarctation of aorta in adults

Abstract: Self-expandable nitinol stents for the treatment of native and recurrent CoA is safe and has good efficacy with acceptable midterm to long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…20 In our study, stent migration during the procedure was reported in 4 patients from the native CoA group. Another known complication of stent implantation is the fracture of endovascular stents.…”
Section: Long -Term Follow -Upmentioning
confidence: 60%
“…20 In our study, stent migration during the procedure was reported in 4 patients from the native CoA group. Another known complication of stent implantation is the fracture of endovascular stents.…”
Section: Long -Term Follow -Upmentioning
confidence: 60%
“…Over the decades, the interventional stenting technology has achieved very fruitful clinical results in treatment of COA, [12,14,20,21] and has become the treatment of rst choice in adults in many centers. [22] However, the stents are not suitable for the coarctation located at the arch of which the curvature is too sharp.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] In spite of that, acute aortic wall injury is often a dramatic event of the stenting technique, and may be more frequent in elderly patients with highly calci ed tissue or hypoplastic vessels with reduced elasticity. [14] In contrast, extra-anatomic bypass could be feasible in all candidates irrespective of COA features.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the stenting technique has gradually replaced the traditional surgical correction of isolated COA in adult patients [ 12 ], attributing to its avoidance of the acute complications caused by thoracotomy and its satisfactory outcomes [ 12 , 13 ]. In spite of that, acute aortic wall injury is often a dramatic event of the stenting technique, and may be more frequent in elderly patients with highly calcified tissue or hypoplastic vessels with reduced elasticity [ 14 ]. In contrast, extra-anatomic bypass could be feasible in all candidates irrespective of COA features.…”
Section: Introductionmentioning
confidence: 99%